1997
DOI: 10.1080/0260293970220402
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Use of Peer Assessment in Higher Education: a case study in the School of Music, Kingston University

Abstract: The following paper outlines and evaluates the implementation of the use of peer assessment in higher education (HE), using the BA in music course at Kingston University as a case study. The rationale of the peer assessment systems introduced into two curriculum areas is examined, and the operation of the scheme is evaluated, by the use of lecturer interviews, attitudinal questionnaires completed by the participating students, and the assessments and feedback produced. Conclusions drawn are that the introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 7 publications
7
112
0
2
Order By: Relevance
“…For example, judgment by peers seems to provide a more significant motivator to produce high-quality work than does the assessment of a single instructor (Searby and Ewers, 1997). As a result, when peers are accountable to each other, the time spent comparing work and discussing ideas and concepts in teams is more productive.…”
Section: Pedagogical Merits Of Peer Assessment and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, judgment by peers seems to provide a more significant motivator to produce high-quality work than does the assessment of a single instructor (Searby and Ewers, 1997). As a result, when peers are accountable to each other, the time spent comparing work and discussing ideas and concepts in teams is more productive.…”
Section: Pedagogical Merits Of Peer Assessment and Evaluationmentioning
confidence: 99%
“…Two of the most prominent were increased confidence in one's performance and increased quality in the learning output. Peer assessment and evaluation also serve to help students take more control over their learning through development of critical analysis of the work of others (Searby and Ewers, 1997). Repeated reading of peer writing, for example, reinforces analysis of one's own work processes and makes the learning more visible to the learner (Topping, Smith, Swanson, and Elliot, 2000).…”
Section: Pedagogical Merits Of Peer Assessment and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the whole process of peer feedback inspires students to be critical, autonomous learners as they become more adept at using feedback criteria and developing a clearer notion of the topic that is assessed (Falchikov, 1995;Searby & Ewers, 1997). If peer feedback is thoughtfully carried out, it can assist the student in developing various learning and life skills, as in learner responsibility, thinking strategies and appraisal skills.…”
Section: Review Of Literature Peer Assessment and Peer Feedback In Gementioning
confidence: 99%
“…It has been suggested that engaging in peerassessment activities might also develop self-assessment skills (Dochy et al, 1999;Somervell, 1993). However, only a few studies have tried to empirically demonstrate that assessing a peer's performance may subsequently improve self-assessment skills (see Oldfield & Macalpine, 1995;Searby & Ewers, 1997).…”
Section: Methodsmentioning
confidence: 99%